ABORTUS PROVOKATUS DALAM ILMU PENGETAHUAN KEDOKTERAN DITIJAU DARI HUKUM PIDANA - Bona Ventura (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTAs a result of this current development, there are some groups of individuals to follow the new developments that are considered modern and leave the old because it is old-fashioned. With the change as it is today, which is experiencing growth often occurs many contradictions either individually or in groups, because the individual or group that there are pros and cons of the change. At the party who wants to oppose or resist the times are headed kepembaharuanakan crushed by renewing itself and would of competition on the teaching reform concerning values and morals. If it turns out such actions constitute a criminal act of abortion provokatus then look for who the perpetrators of such acts. The subsequent police search for explanations to the people who know the act was committed, nor evidence as conclusive evidence. Furthermore, police did arrest the person who did the deed. Similarly, laws concerning the interests of health, many are no longer relevant to protect the parties in the healthcare system with advanced technology. Finally the criminal law by law enforcement officers, are required to be more creative in studying and following the development of modern law that always adjusts development and social change in society